Aspects associated with waterpipe smoking in Iranian youths: a qualitative study - Hamid Jafaralilou; Arman Latifi; Mehdi Khezeli; Atefeh Afshari; Farahnaz Zare (BMC, 2021)
Abstract Background Waterpipe is one of the oldest methods of tobacco smoking, which has become the public health challenge, especially in the Eastern Mediterranean countries such as Iran. This study aimed to investigate the waterpipe smoking (WPS) in the young people of Kermanshah in 2020, using a qualitative method. Methods This was a qualitative study conducted with the approach of content analysis. Participants were young waterpipe user aged 17 to 25 years selected by purposeful sampling method in Kermanshah city, located in the west of Iran. Data were collected through semi-structured interviews in face-to-face and audio-recorded methods based on an interview guideline during June to August 2020. Then researchers transcribed verbatim and analyzed the content of the interviews thematically. Results In this study, 23 young people who were waterpipe users at the time of the study participated. The results showed that social aspects in three sub-categories were involved in WPS including "socio-cultural aspects", "socio-environmental aspects", and "social relations". Individual aspects of waterpipe use as second category also consisted of two sub-categories including "motivational aspects" and "lack of psycho-protective aspects". Conclusions It seems that the implementation of the policy of reducing access to waterpipe in public environments is effective in reducing waterpipe consumption. It is suggested that educational and interventions, based on targeted models and theories be implemented in order to increase young people's belief and perception on dangers of WPS, and to improve their self-efficacy to smoking cessation.